2022
DOI: 10.3390/life12030447
|View full text |Cite
|
Sign up to set email alerts
|

Abdominopelvic Actinomycosis—The Diagnostic and Therapeutic Challenge of the Most Misdiagnosed Disease

Abstract: Abdominopelvic actinomycosis is a rare chronic or subacute bacterial infection caused by Actinomyces israelii, a Gram-positive anaerobic bacterium that normally colonizes the digestive and genital tracts, clinically presented as an inflammatory mass or abscess formation. Methods: We reviewed the medical records of the patients from our clinic with abdominopelvic actinomycosis who underwent surgery between 2002 and 2022. In this period, 28 cases (9 men and 19 women) were treated. The mean age was 43.36 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The colonization rate increases with the duration of its maintenance. 2 , 5 Vasilesco et al 6 reviewed the medical records of 28 patients with abdominopelvic actinomycosis (9 men and 19 women) and the cause of actinomycosis in the studied group was an IUD device in 17 cases from which, 6 patients were admitted because they mimicked a complicated abdominopelvic malignant ovarian advanced ovarian cancer. To reduce the occurrence of this affection, it is recommended that IUDs be changed periodically, every 3–5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The colonization rate increases with the duration of its maintenance. 2 , 5 Vasilesco et al 6 reviewed the medical records of 28 patients with abdominopelvic actinomycosis (9 men and 19 women) and the cause of actinomycosis in the studied group was an IUD device in 17 cases from which, 6 patients were admitted because they mimicked a complicated abdominopelvic malignant ovarian advanced ovarian cancer. To reduce the occurrence of this affection, it is recommended that IUDs be changed periodically, every 3–5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Further delineation from malignancy maybe done by careful evaluation of cross-sectional imaging. Firstly, due to the size of the bacterium it does not easily spread via lymphatics [14] . Therefore, although the infiltrative nature of these infections closely mimic neoplasms on CT, the paucity of lymphadenopathy despite the significant “tumour” burden is characteristic of actinomycosis [14] , [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, due to the size of the bacterium it does not easily spread via lymphatics [14] . Therefore, although the infiltrative nature of these infections closely mimic neoplasms on CT, the paucity of lymphadenopathy despite the significant “tumour” burden is characteristic of actinomycosis [14] , [15] . Notably, in the index case only 15 nodes were retrieved despite the extent of en block resection.…”
Section: Discussionmentioning
confidence: 99%
“…Having diabetes mellitus increases a patient’s risk of contracting gastrointestinal infections [ 8 ]. According to retrospective studies conducted among 41 patients with abdominal actinomycosis, seven cases showed an association with diabetes [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinical pictures and imaging modalities are not always adequate in differentiating malignancy from inflammatory conditions for a variety of reasons, leading to a 10% lower rate of presurgical diagnosis [ 1 ]. In the literature from 2002 to 2022, twenty-eight cases were reported with abdominal actinomyces in patients who underwent surgery, with only two cases that have received a preoperative diagnosis [ 4 ]. Another literature review from 1980 to 2018 showed thirteen cases that have been postoperatively diagnosed after histopathological and microbiological assessment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%